Effects of STING stimulation on macrophages: STING agonists polarize into “classically” or “alternatively” activated macrophages? - Ohkuri, Takayuki (Hum Vaccin Immunother, 2017)
Stimulator of interferon genes (STING) was defined as an important molecule for promoting antitumor immunity through mediating type I interferon (IFN) production by sensing its ligands such as cyclic GMP-AMP (cGAMP). Our recent study indeed demonstrated that intratumoral injection of cGAMP showed effective antitumor responses via accumulating activated macrophages in the tumor microenvironment in a STING-dependent manner. Because the antitumor effect of cGAMP was abrogated when macrophages were depleted, the existence of the activated macrophages in the tumor site would be important for effective antitumor immune responses. Macrophages show phenotypic diversity and plasticity and are categorized into several groups by stimulation factors, e.g. IFN-γ and IL-4 for M1 and M2 macrophages, respectively. However, the impact of STING stimulation on the macrophage activation status remains to be evaluated. Here we summarize the complex polarized status of macrophages and the signaling cascade triggered by STING stimulation and also discuss the impact of STING signaling on the macrophage activation status for future directions.